trig

posted by .

How do I prove these trig identities?
secx-cosx/tanx =sinx

And

1+sinx/cosx+ cox/ 1+sinx=2secx

  • trig -

    I will show you the first problem to give you an idea how to approach proving trig identities.

    Here are a few basic identities that will help:

    sinx/cosx = tanx
    secx = 1/cosx
    cos^2x + sin^2x = 1

    Let's put everything into sine and cosine form and work the left hand side:

    (secx - cosx)/tanx = sinx
    (1/cosx - cosx)/(sinx/cosx) = sinx
    (1/cosx - cosx)(cosx)/sinx = sinx
    (cosx/cosx - cos^2x)/sinx = sinx
    (1 - cos^2x)/sinx = sinx
    sin^2x/sinx = sinx
    sinx = sinx

    And there you have it!

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Pre-Calc

    Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
  2. Simplifying with Trigonometry Identities

    Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each other. …
  3. Trigonometry.

    ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side …
  4. Trig........

    I need to prove that the following is true. Thanks (cosx / 1-sinx ) = ( 1+sinx / cosx ) I recall this question causing all kinds of problems when I was still teaching. it requires a little "trick" L.S. =cosx/(1-sinx) multiply top and …
  5. Mathematics - Trigonometric Identities

    Prove: sinx + tanx = tanx (1 + cosx) What I have so far: LS: = sinx + tanx = sinx + (sinx / cosx) = (sinx) (cosx) + sinx / cos = tanx (cosx + sinx) I don't know what to do now
  6. Mathematics - Trigonometric Identities

    Prove: (tanx)(sinx) / (tanx) + (sinx) = (tanx) - (sinx) / (tanx)(sinx) What I have so far: L.S. = (sinx / cosx) sinx / (sinx / cosx) + sinx = (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx) = (sin^2x / cosx) / (cosx / sinx + sinxcosx)
  7. Trigonometry Check

    Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] = [cosx(1-sinx]/[cosx(1+tanx] …
  8. Math

    Im really struggling with these proving identities problems can somebody please show me how to do these?
  9. Math

    I'm only aloud to manipulate one side of the problem and the end result has to match the other side of the equation Problem 1. sinx + cosx + sinx + tanx + cosxcotx = secx + cscx Problem 2. ((sinx + cosx)/(1 + tanx))^2 + ((sinx - cos^2x)/(1 …
  10. Precalculus/Trig

    I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1 - cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1-cosx Simplified: cosx + sin^3x/sin^3x = cscx/1-cosx I don't know …

More Similar Questions